THE HISTORY FORMATION OF THE SCIENCE OF ABAI STUDIES - Kurmangalieva, Gulnur (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The article will focus on the history of the formation of one of the fundamental branches of Kazakh literary science – Abay studies. An overview of the history of the formation and study of the history of Abay studies is made, scientific works that have shown the heritage of Abay in different years are analyzed. In the main part, a brief analysis of the history of Abai's knowledge, the study of the poet's heritage in general, a lot of scientifically valuable historical facts are analyzed. Through the work of scientists studying the history of Abay studies, the personality and civic identity of the poet are revealed. After studying the research of research scientists in research works and monographs, the importance and effectiveness of the modern discipline of Abay studies is shown. The history of the study and the stages of the formation of Abay studies are differentiated in modern times, when the degree of research of data on the heritage of Abay is increasing. Starting with M. Auezov, who brought Abay studies into the scientific system, based on the works of Y. Mustambayevich, K. Zhubanov, B. Kenzhebayev, K. Zhumaliyev, Z. Akhmetov, K. Mukhamedkhanov, M. Myrzakhmetuly, it is necessary to look at the history of the formation of Abay studies and analyze the works of the independence period from a new angle.